“LİMON KIZ” MASALININ SEMBOLİK ÇÖZÜMLEMESİ - Çetindağ Süme, Gülda (Motif Akademi Halk Bilimi Dergisi, 2024)
Fairy tales, which constitute an important area of our spiritual wealth, are products that both shape our identity in terms of national values and folklore elements such as the subject matter, language used, vocabulary, dialect, traditions and customs, customs and traditions, clothing-dressing, beliefs, etc. and help to analyze the codes in our cultural codes. The fairy tale, which assimilates the truth and brings it together with the language of symbols and is a part of cultural identity, has found a meaningful place for itself with its various features and in the tradition of telling. All the meanings contained in fairy tales also open the doors of an invisible world as much as possible. From this point of view, considering the symbolic and mythological aspects of fairy tales in addition to their apparent meanings will be an important step in learning our cultural heritage left by our ancestors. The fairy tale named Lemon Girl, which we will evaluate in terms of symbolic and mythological elements in our study, is one of the fairy tales that are widely told and variantized in Turkish fairy tales and that give messages with symbolic and mythological references. When the symbolic meanings of the fairy tale, which has variants with many different names such as Three Lemon Girls, Pomegranate Girl, Three Pomegranates, Three Pomegranates, Three Pomegranates, Three Pomegranates, Three Pomegranate Beauty, Three Watermelon Beauty, Three Apples in Anatolia, the unlimited richness of our culture, which is passed down from generation to generation, will be tried to be revealed. The motifs with symbolic value in the fairy tale will be analyzed and the meanings that the fairy tale wants to tell will be evaluated comparatively.